WHERE DYSTOPIA BECOMES REALITY AND UTOPIA NEVER COMES - öztürk, abdulserdar -; suljic, vesna (Journal of History Culture and Art Research, 2013)
Abstract The article Where Dystopia Becomes Reality and Utopia Never Comes draws a comparison between utopian and dystopian visions of the world described in two works by Aldous Huxley (1894-1963): Brave New World and Island and a fine line where the author’s farsightedness crosses over the boundaries of imagination and turns into reality of the twentyfirst century. Composed as a satire of the world in the 1930s and as a response to H. G. Wells’ “utopias of horror”, Brave New World displays Huxley’s ingenuity in being a sharp and articulate critic of the contemporary society; warning of the dangers of abuse of science in hands of unconstrained establishments of power; and perspicuity of ideologies, mass consumerism, and influences of the media. Prophecies of Brave New World have become realities of our time in many instances, whereas ideals of Island are still in the dreamtime. Öz Gerçekleşen Distopya Fakat Asla Gerçekleşmeyen Ütopya başlıklı bu makale, Aldous Huxley (1894-1963) tarafından kaleme alınan Cesur Yeni Dünya ve Ada adlı romanlarında ortaya konan ütopya ve distopya kavramlarını karşılaştırmaktadır. Yazarın uzak görüşlülüğü tahayyül sınırlarını aşarak yirmibirinci yüzyılda gerçeğe dönüşür. 1930’ların dünyasına bir eleştiri olarak yazılan ve H. G. Wells’in dehşet ütopyasına bir cevap olan Cesur Yeni Dünya, Huxley’in çağdaş toplumun ustalıklı ve kesin bir eleştirisini, kontrolsüz gücün elinde bilmin kötü amaçlar için kullanılma tehlikesini, belli ideolojileri, kitle tüketimlerini ve medyanın etkilerini gözler önüne serer. Cesur Yeni Dünya’nın kehanette bulunduğu bir çok olay günümüzde gerçeklemişken, Ada’da ortaya konan idealler hala hayal olmaktan öteye gidememiştir.